Introduction of pseudo-halide (SCN−) in CH3NH3PbI3 perovskite films : effect on moisture stability - Teo, Royston Wei Jin (2016)
Recently perovskite solar cells have been a popular area of photovoltaic solar cells research due to its cost and ease of fabrication. It has seen the fastest growth in the area of efficiency, from 3.8 % to 21% efficiency (Michael Saliba, 2016) achieved today. Compared to conventional first generation silicon solar cells, fabrication of the perovskite solar cell is faster and cheaper to reproduce due to the precursors are simple solutions and the techniques such as spin-coating and annealing thin films. However, a limitation of the perovskite solar cells is the stability issues that it faces, mainly due to moisture. This area of stability is not yet developed in research and not much is understood about the degradation pathways and mechanisms. In this report, we tackle the issue of moisture stability by introducing a pseudo-halide (thiocyanate (SCN-)) into the methyl ammonium lead iodide (CH3NH3PbI3 (MALI)) perovskite. Accordingly, we have prepared perovskite films by adding methyl ammonium iodide (MAI) and lead(II) iodide PbI2 and lead thiocyanate Pb(SCN)2 precursors (in various mole ratios) to study the moisture stability of the perovskites. We have also explored possibility of perovskite formation by mixing the MAI and Pb(SCN)2 precursors in various molar ratios namely 1:1, 2:1 and 4:1. The perovskite films were characterized using various characterisation techniques such as UV Vis to determine the light absorption capabilities of the film, XRD to characterize the formation of different phases in the film, and FE-SEM to observe the morphology of the film. We have observed an improved moisture stability for the perovskite films by the addition of SCN- in perovskite (MALI) films as compared to the standard perovskite MALI films.